The influence of self-owned home blood pressure monitoring (HBPM) on primary care patients with hypertension: A qualitative study - Abdullah, Adina; Othman, Sajaratulnisah (BMC, 2011)
Background: Home blood pressure monitoring (HBPM) is gaining popularity among hypertensive patients. This study aimed to explore the influence of self-initiated HBPM on primary care patients with hypertension. Methods: Six in-depth interviews and two focus group discussions were conducted, taking into consideration the experiences of 24 primary care patients with hypertension. These patients had been using HBPM as part of their hypertension management. The overriding influences were grouped under themes which emerged from analyzing the data using the grounded theory approach. Results: There are both positive and negative influences of self-initiated HBPM. Patients used the readings of their HBPM to decide on many aspects of their hypertension management. The HBPM readings both influenced their adherence to diet and exercise and provided certain reassurance when they experienced symptoms. In addition, the act of discussing their HBPM readings with their health care providers resulted in an enhanced doctor-patient therapeutic relationship. Nevertheless, HBPM created confusion at times in some patients, particularly with regard to the target blood pressure level and the need for medication. This led to some patients making their own medical decisions based on their own standards. Conclusions: HBPM is becoming an integral part of hypertension management. Primary care patients who self-initiated HBPM reported being more self-efficacious, but lack of participation and guidance from their doctors created confusion, and hindered the true benefit of HBPM.